Analisis Zakat Fitrah dan Zakat Mal dalam Islam - F, Fatmawati; M, Misbahuddin; Sanusi, Muh. Nur Taufik (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The problem of Islam is a balanced and integrated view of life designed to usher in human happiness through increasing human needs through human moral and material needs, and acculturation of socio-economic relations and brotherhood between societies.  This can be reflected in the practice of worship, for example in Zakat worship because it includes these two elements, namely social and economic Muslim communities in general. What drives the writing of this journal is the intention of niat. To give advice and warning about the obligation of zakat which most Muslims have underestimated, they do not issue it in the prescribed way, even though it is a great matter, and is one of the five pillars of Islam which the edifice of Islam would not stand without." Islam is built on five foundations: the Creed that there is no God but Allah, and Muhammad the messenger of Allah, upholds prayer, performs zakat, fasts Ramadan and Hajj". This shows that zakat